EFFECTIVENESS OF AUDIO VISUAL AIDS (AVA) BASED EDUCATION ON PATIENTS' KNOWLEDGE AND ANXIETY PRE CATARACT OPERATION - Nizar, Angga Miftakhul; Purnomo; Suciati; Maksum; Diana Ani Porwati; Dewi Siyamti (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: One of the treatments for cataracts is surgery. Lack of knowledge of precataract surgery patients can cause fear, anxiety and stress, because it can threaten the integrity of the body, soul and can cause pain. The purpose of the study was to determine the effect of audio visual education on the cataract surgery process on the knowledge and anxiety of precataract surgery patients at Tulungagung hospital Method: This study was conducted on July 15-August 10, 2024 using the pre- experimental design method with a one group pretest posttest design approach. population of all pre-cataract surgery patients at RS Tulungagung underwent surgery on July-August 2024, samples were taken using accidental sampling techniques of 40 respondents Result: in this study with statistical test showed that there was an effect of audio visual education of the cataract surgery process on the knowledge of pre-cataract surgery patients (0.000 <0.05) and anxiety of pre-cataract surgery patients (0.000<0.05) at Tulungagung Hospital in 2024. Conclusion : Audio-visual-based health education carried out by health workers as people who are proven in the health field is very useful in increasing knowledge and reducing anxiety of pre-cataract surgery patients